On singular foliations on the solid torus - Arraut, José L.; Martins, Luciana F. [UNESP]; Schütz, Dirk (Elsevier, 2013)
We study smooth foliations on the solid torus S1×D2 having S1×{0} and S1×∂D2 as the only compact leaves and S1×{0} as singular set. We show that all other leaves can only be cylinders or planes, and give necessary conditions for the foliation to be a suspension of a diffeomorphism of the disc. © 2013 Elsevier B.V.
Keywords: Foliations; Solid torus; Vector fields